Editorial Vol12 no1 - Graham Connelly (Scottish Journal of Residential Child Care)
The first issue of the Scottish Journal of Residential Child Care (SJRCC) was published, in hard-copy format, and posted out to subscribers, on 18 August 2002. Eleven years later, and after a short sabbatical to take stock, SJRCC is back, refreshed and available as a free-to-download online journal.